Determinants of E-Banking in Nepal - Adhikari, Kamal Prakash (Management Dynamics, 2019)
This study tries to examine the determinants of e-banking in Nepal. Descriptive and causal research design was used in this study. Primary cross-section data were collected. Non-random sampling method was applied in this study. One hundred structured questionnaires were administered to respondents to gather data. This research confirmed that convenience, time savings, security and communication are the determinants of e-banking in Nepal.